Oxidation of refractory sulfur-containing compounds with molecular oxygen catalyzed by vanadoperiodate. Issue 2 (8th December 2014) - Tang, Nanfang; Jiang, Zongxuan; Li, Can
Abstract : [C8 H17 N(CH3 )3 ]3 HIV9 O28 has been first synthesized by a simple, one-pot stoichiometric reaction, which shows high catalytic activity in oxidation of refractory sulfur-containing compounds to their corresponding sulfones using molecular oxygen under mild reaction conditions. Abstract : A new vanadoperiodate [HIV9 O28 ] 3− has been synthesized by a simple, one-pot stoichiometric reaction of HIO4 ·2H2 O with NaVO3 in aqueous solution and then isolated as [C8 H17 N(CH3 )3 ]3 HIV9 O28 by cation exchange. We have found that [C8 H17 N(CH3 )3 ]3 HIV9 O28 shows high catalytic activity in the oxidation of refractory sulfur-containing compounds to their corresponding sulfones using molecular oxygen as oxidant under mild reaction conditions.